2005
DOI: 10.3748/wjg.v11.i45.7118
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of ω-3 fatty acid supplementation in addition to mesalazine in maintaining remission in pediatric Crohn's disease: A double-blind, randomized, placebo-controlled study

Abstract: Enteric-coated omega-3 FAs in addition to treatment with 5-ASA are effective in maintaining remission of pediatric CD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
57
0
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(60 citation statements)
references
References 28 publications
1
57
0
2
Order By: Relevance
“…Moreover, administration of entericcoated capsules without unpleasant taste and side effects resulted in a high compliance of patients. The content of the capsules is delivered directly into the small intestine (Belluzzi et al, 1996;Romano et al, 2005). Our finding of a substantial increase in EPA in membrane phospholipids is consistent with previous reports on ALA supplementation.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Moreover, administration of entericcoated capsules without unpleasant taste and side effects resulted in a high compliance of patients. The content of the capsules is delivered directly into the small intestine (Belluzzi et al, 1996;Romano et al, 2005). Our finding of a substantial increase in EPA in membrane phospholipids is consistent with previous reports on ALA supplementation.…”
Section: Discussionsupporting
confidence: 91%
“…Although clinical evidence suggests that the increased intake of n-3 PUFA enhances anti-inflammatory capacity and diminishes disease activity in patients with maldigestion and malabsorption (Belluzzi et al, 1996;Romano et al, 2005), the responsible mechanism of action remains unclear. The aim of this study was to assess the hypothesis that oral supplementation of specific fatty acids (such as mediumchain triglycerides and selected n-3 PUFAs) increases their incorporation into erythrocyte membrane phospholipids in patients with maldigestion and/or malabsorption.…”
Section: Introductionmentioning
confidence: 99%
“…It is induced by tumor necrosis factor (TNF)-α and IL-1β activation and is characterized by neutrophil mucosal infiltration (4,9). Most rodent models of UC based on DSS administration employ concentrations between 3% and 7% DSS in drinking water (13,(17)(18)(19)(20)(21)(22) In our study, after 8 days of 5% DSS administration in all groups, the colonic mucosa appeared hyperemic, edematous with hemorrhagic erosions and tiny blood coagula.…”
Section: Discussionmentioning
confidence: 90%
“…Clinical intervention studies and animal experiments showed that N3PUFAs have anti-inflammatory properties (3), which are based on their ability to antagonize the activity of arachidonic acid, thereby reducing the production of inflammatory and chemotactic derivatives and suppressing cell-mediated immune responses (3,4). Furthermore, N3PUFAs suppress leukocyte activity, cell proliferation, inflammatory cytokine synthesis, natural killer cell activity, antibody synthesis and macrophage surface membrane protein expression (5), and they also act as free radical scavengers (6).…”
Section: Introductionmentioning
confidence: 99%
“…Studies in which olive oil have been used as a placebo have reported contradictory results. Lorenz et al have shown an increased activity of disease in patients of ulcerative colitis and Crohn's disease supplemented with olive oil as a placebo versus fish oil group (Lorenz et al, 1989;Romano et al, 2005). However others authors have not founds differences between both groups of supplementation (Greenfield et al, 1993;Trebble et al, 2005).…”
Section: Trials In Human Patientsmentioning
confidence: 93%